2020
DOI: 10.1136/bcr-2019-230884
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu arteritis in a rural hospital in Indonesia

Abstract: Takayasu arteritis (TA) is a rare chronic granulomatous inflammation of the aorta or its branches and is prevalent all around the world. It causes stenosis of large arteries and ischaemic damage to target organs. There is usually a delay in recognising TA because of the rarity and unfamiliarity with the disease, unspecific early symptoms and lack of diagnostic equipment for early diagnosis. In this report, we present a case of an 18-year-old woman from Pasuruan, East Java, Indonesia, with recurrent fever, head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Following are the six components of the criteria 1) age of 40 years or younger at disease onset 2) claudication of the extremities 3) decreased pulsation of one or both brachial arteries 4) difference of at least 10 mmHg in systolic Blood pressure between arms 5) bruit over one or both subclavian arteries or the abdominal aorta 6) arteriographic narrowing or occlusion of the entire aorta, its primary branches, or large arteries in the upper or lower extremities that is not due to arteriosclerosis, fibromuscular dysplasia, or other courses. Presence of three or more of six criteria supports the diagnosis of TAK with the sensitivity of 90.5% and the specificity of 97.8% (5). According to Takayasu conference held in Tokyo in 1994 (5,6), TAK is sub-grouped into six types according to angiographic findings of arterial involvement as follows, type I-branches from the aortic arch; type IIa-ascending aorta, aortic arch and it's branches; type IIb-ascending aorta, aortic arch and its branches, thoracic descending aorta; type III-thoracic descending aorta, abdominal aorta, and/or renal arteries; type IV-abdominal aorta and/or renal arteries; type V-combined features of types IIb and IV.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Following are the six components of the criteria 1) age of 40 years or younger at disease onset 2) claudication of the extremities 3) decreased pulsation of one or both brachial arteries 4) difference of at least 10 mmHg in systolic Blood pressure between arms 5) bruit over one or both subclavian arteries or the abdominal aorta 6) arteriographic narrowing or occlusion of the entire aorta, its primary branches, or large arteries in the upper or lower extremities that is not due to arteriosclerosis, fibromuscular dysplasia, or other courses. Presence of three or more of six criteria supports the diagnosis of TAK with the sensitivity of 90.5% and the specificity of 97.8% (5). According to Takayasu conference held in Tokyo in 1994 (5,6), TAK is sub-grouped into six types according to angiographic findings of arterial involvement as follows, type I-branches from the aortic arch; type IIa-ascending aorta, aortic arch and it's branches; type IIb-ascending aorta, aortic arch and its branches, thoracic descending aorta; type III-thoracic descending aorta, abdominal aorta, and/or renal arteries; type IV-abdominal aorta and/or renal arteries; type V-combined features of types IIb and IV.…”
Section: Discussionmentioning
confidence: 96%
“…Presence of three or more of six criteria supports the diagnosis of TAK with the sensitivity of 90.5% and the specificity of 97.8% (5). According to Takayasu conference held in Tokyo in 1994 (5,6), TAK is sub-grouped into six types according to angiographic findings of arterial involvement as follows, type I-branches from the aortic arch; type IIa-ascending aorta, aortic arch and it's branches; type IIb-ascending aorta, aortic arch and its branches, thoracic descending aorta; type III-thoracic descending aorta, abdominal aorta, and/or renal arteries; type IV-abdominal aorta and/or renal arteries; type V-combined features of types IIb and IV. Our patient fulfilled four criteria to make the diagnosis of Takayasu arteritis, type V.…”
Section: Discussionmentioning
confidence: 96%
“…The condition is prevalent worldwide, with Asia having the highest frequency [ 10 ]. Japan estimated roughly 150 new TA cases a year [ 13 ]. The aorta, branches, and pulmonary arteries are all affected by the chronic inflammatory condition known as TA.…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography (CTA) is more commonly employed as it allows the study of wall inflammation [2]. NMR (nuclear magnetic resonance) angiography and 18F fluorodeoxyglucose positron emission tomography (18F FDG-PET) are recent, more favorable techniques as they aid in the diagnosis of TA even in the pre-stenotic phase by detecting structural wall changes [3,13]. They are also useful for evaluating the response to treatment in TA [2].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had approximately a six-month delay. It has also been reported that 91% of patients claim to have been seen by at least one doctor before diagnosis [13]. Furthermore, most rural hospitals do not have the availability of non-invasive imaging modalities such as magnetic resonance angiography (MRA), CTA, and FDG-PET [13].…”
Section: Discussionmentioning
confidence: 99%